Aliran Filsafat Hukum Sebagai Cara Pandang (Worldview) Hakim Dalam Menjatuhkan Putusan Pidana - Asa, Agam Ibnu; Syamsuddin, Muhammad Mukhtasar; Wahyudi, Agus; Hamzah, Agus (Jurnal Pembangunan Hukum Indonesia, 2025)
The development of modern legal science requires a strong philosophical foundation to address the complexities of contemporary legal issues. The philosophy of law functions not only as a theoretical reflection but also as a fundamental basis for building legal theory and judicial practice. This study aims to examine the role of the philosophy of law in the development of legal science and theory, and how various schools of the philosophy of law, including Natural Law, Utilitarianism, the Historical School, Sociological Jurisprudence, Legal Realism, Critical Legal Studies (CLS), Feminist Legal Theory (FLT), Responsive Law, and Progressive Law, shape judges' worldviews in delivering criminal verdicts. This research uses a juridical-philosophical method with a conceptual and normative approach. The results show that the philosophy of law plays a central role in testing the validity, methodology, and truth within legal science. Moreover, the application of various legal thought schools enables judges to balance legal certainty with substantive justice, while considering social dynamics and the moral values of society. This study concludes that the philosophy of law is not only a theoretical framework but also serves as an integral worldview for judges in enforcing law that is just and responsive to social changes.